Показатели социального неблагополучия украинских регионов - Левцун, А.; Лысак, Н. (Социология: теория, методы, маркетинг, 2000)
The methods of measurement of social trouble are considered. It is analyzed possessed experience; the new ways of account of an index of social trouble are offered. On the basis of the received parameters, are investigated a level and features of social trouble of the Ukrainian regions. The correlation of parameters of social trouble with electoral behavior is considered.